Does education and skills affect productivity? (study on Pontianak Pelindo) - Damayanti, Fera; Bintoro Bagus Purmono; Fahmi, Fitri Fadilah; Qisthi Ardhi (Jurnal Ekonomi, 2024)
This study aims to determine the effect of education and skills on employee work productivity. The data was obtained in the form of primary data and secondary data. Questionnaires were distributed to one of the state-owned companies in Pontianak, namely PT Pelabuhan Indonesia (Persero) Regional 2 Pontianak. The number of samples used in the study was 51 respondents. Data collection techniques were used by distributing questionnaires and processed using SPSS 25 Statistics. This study uses a quantitative descriptive method and uses multiple linear regression analysis. This research also uses data quality tests, classical assumption tests, and hypothesis tests in the form of t-test, F test, and coefficient of determination (R2). The results show that education does not affect employee work productivity. While skills affect employee work productivity